International migration, COVID-19, and environmental sustainability - Chatterji, Manas; Luterbacher, Urs; Fert, Valérie; Chen, Bo (Contributions to conflict management, peace economics and development ;, 2023)
International migration afflicts nearly every corner of the globe, from the Americas, Europe and North Africa, and adjoining countries in South Asia. This migration links the socio-economic statuses of migrants' home countries and those into which they are migrating. This phenomenon has a profound impact upon ethnic conflict, resource availability, famines and other natural and manmade disasters, as well as financial, political, social and environmental implications for some of the world's most seemingly unsolvable crises, such as world peace. These vast complexities have been further exemplified by the COVID-19 pandemic, which, as analysed through an environmental and migratory lens, is the focus of this 32nd volume of the book series Contributions to Conflict Management, Peace Economics and Development. With contributions from world-renowned scholars, International Migration, COVID-19, and Environmental Sustainability tackles recent universal subject matter and ties it to key contemporary issues, including globalisation and sustainability, that are related to international migration and its impacts.